An experimental chimeric hepatitis E virus vaccine elicits both local and systemic immune responses - Müller, Melisa Florencia; Sacur, Jacinto; Brancher, Julia Matias; Vera, María Daniela; Arce, Lorena; Raya-Tonetti, María Fernanda; Kitazawa, Haruki; Villena, Julio; Vizoso-Pinto, María Guadalupe (Frontiers in Microbiology, 2024)
IntroductionThe development of a hepatitis E virus (HEV) vaccine is critical, with ORF2 capsid protein as the main target. We previously demonstrated that oral coadministration of recombinant ORF2 with immunomodulatory bacterium-like-particles (IBLP) induces a specific immune response in mice, particularly using IBLP derived from Lacticaseibacillus rhamnosus IBL027 (IBLP027), which was effective in eliciting a local humoral response. IBLP are non-live bacteria with adjuvant and carrier properties, serving as a platform for exposing proteins or antigens fused to LysM (lysine motif) domains, protein modules that bind to cell wall polysaccharides like peptidoglycan.MaterialsWe cloned the most immunogenic domain of ORF2 (O2P2) fused to five LysM domains (LysM5O2P2) and displayed this chimeric protein on the surface of IBLP027 to create a prototype vaccine (IBLP027-LysM5O2P2). We evaluated its capacity to induce an immune response in vivo by immunizing mice with three doses of either the experimental vaccine or the chimeric protein alone, using an oral or a combined schedule with subcutaneous priming followed by oral boosting. Control groups received IBLP027. Sera and small intestine fluid were analyzed for humoral response, while Peyer’s patches and spleen immune cells were used for ex vivo stimulation with capsid protein to assess cellular response.ResultsThe oral scheme failed to elicit an IgG response, but this was overcome by a subcutaneous priming dose followed by oral boosters, which led to increasing IgG titers in the combined scheme. The highest IgG titers were seen in the vaccine prototype group. Most groups produced significantly higher IgA levels in intestinal fluid, especially in those that received the oral scheme. Cellular response studies showed increased tumor necrosis factor (TNF)-α, interferon (IFN)-γ interleukin (IL)-4, and IL-17 levels in groups receiving the chimeric protein via oral or combined schedules.ConclusionFurther and continuous research is needed to better understand both the needs and expectations of students and supervisors in different academic realities, including in Veterinary Medicine schools, from which the information available on the subject is scarce.